Assessing the impact of virtual workplaces on collaboration and learning - Sánchez Rodríguez, Irene; Bailo, Luca; Panizza, Folco; van Es, Valerie A. A.; Alessi, Marzio; Betta, Monica; Ricciardi, Emiliano (Frontiers in Psychology, 2025)
IntroductionThe shift toward remote work and digitization has driven the widespread adoption of virtual collaboration tools. While these technologies offer opportunities for enhanced remote interaction, they also present challenges related to communication, security, and social dynamics. Understanding how different digital environments impact collaboration and learning is crucial as workplaces evolve.MethodsThis study investigated the impact of four workplace environments—physical presence, videoconferencing, non-immersive Metaverse, and immersive Metaverse—on task performance, cognitive engagement, ergonomics, and social dynamics. A total of 103 participants performed an “active” social decision-making task and a “passive” information retention task. Behavioral and electrophysiological data (EEG-based indices of concentration, fatigue, and relaxation) were collected to assess cognitive and emotional states.ResultsVirtual environments supported collaboration comparably to physical presence. However, immersive environments (Metaverse VR+) were associated with reduced concentration and increased cognitive load, particularly during passive learning. Female participants exhibited higher attentional focus across conditions, and older participants outperformed younger ones in certain tasks. Ergonomic factors such as device comfort and ease of use significantly influenced concentration and relaxation.DiscussionWhile virtual platforms can replicate many aspects of physical presence, key differences persist in cognitive load, comfort, and engagement—especially in immersive settings. These findings highlight the potential and limitations of technologies like the Metaverse in supporting remote collaboration and learning, emphasizing the need for thoughtful design to reduce fatigue and enhance usability.